A Genetic Model for Understanding Higher Order Visual Processing: Functional Interactions of the Ventral Visual Stream in Williams Syndrome - Sarpal, Deepak (Oxford University Press, 2008)
Williams syndrome (WS) is a rare neurodevelopmental disorder caused by a 1.6 Mb microdeletion on chromosome 7q11.23 and characterized by hypersocial personality and prominent visuospatial construction impairments. Previous WS studies have identified functional and structural abnormalities in the hippocampal formation, prefrontal regions crucial for amygdala regulation and social cognition, and the dorsal visual stream, notably the intraparietal sulcus (IPS). Although aberrant ventral stream activation has not been found in WS, object-related visual information that is processed in the ventral stream is a critical source of input into these abnormal regions. The present study, therefore, examined neural interactions of ventral stream areas in WS. Using a passive face- and house-viewing paradigm, activation and functional connectivity of stimulus-selective regions in fusiform and parahippocampal gyri, respectively, were investigated. During house viewing, significant activation differences were observed between participants with WS and a matched control group in IPS. Abnormal functional connectivity was found between parahippocampal gyrus and parietal cortex and between fusiform gyrus and a network of brain regions including amygdala and portions of prefrontal cortex. These results indicate that abnormal upstream visual object processing may contribute to the complex cognitive/behavioral phenotype in WS and provide a systems-level characterization of genetically mediated abnormalities of neural interactions.